A descriptive study of the space utilization of selected Filipino families living in small apartment spaces - Cabatac, Raquel Angelique M.; Quevedo, Ma. Teresa P. (2010.)
The research examined how selected Filipino families managed limited residential spaces. It studied how these families utilized the living and dining areas of their small apartment units. A multi-method approach was employed in the study: observation, interview, and photo-documentation were used in gathering data. Purposive sampling was used to select the 5 apartment units to be studied. Each unit was occupied by a family having 4 to 7 members. Ten representative family members were requested to answer the questionnaire while 1 member from each family was interviewed. The instruments of the study included observation guides, camera, sketch pad, measuring tape, interview guide, and questionnaire. Results showed that Filipino residential spaces are becoming more practical in terms of space utilization and furniture use. The living and dining areas of the selected apartment units had minimal but multifunctional furniture pieces. The families maintained the traditional functions of the areas as places for entertaiment and eating, respectively. The other factors that affected the utilization of space were number of family members, personal preferences, practical needs, age, family composition, and budget. The selected families adapted more practical and modern ideas in the space utilization of their living and dining areas. In some ways, the strategies adopted by the selected families were able to satisfy their practical needs as well as the functional requirements of their living and dining areas. However, the current strategies in space utilization are not very effective due to lack of motivation and budget.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Apartment houses -- Philippines -- Designs and plans; Apartment houses -- Space utilization